A new armored dinosaur with double cheek horns from the early Late Cretaceous of southeastern China - Lida Xing; Kecheng Niu; Jordan Mallon; Tetsuto Miyashita (Vertebrate Anatomy, Morphology, Palaeontology, 2024)
Ankylosaurines are the iconic armoured dinosaurs that characterize terrestrial vertebrate faunas in the Late Cretaceous of Asia and Laramidia (western North America). The earliest members of this clade are known from the early Late Cretaceous (Cenomanian–Santonian) times of Asia, but little consensus has emerged as to how they are related to the anatomically derived and chronologically younger forms. In southeastern China, the Cretaceous red sand beds crop out across basins from Zhejiang to Guandong provinces. However, the horizons corresponding to the early Late Cretaceous stages remain poorly sampled. Here, we report the first definitive vertebrate skeleton ¾ let alone that of an armoured dinosaur ¾ from the Coniacian/Turonian Ganzhou Formation, Datai yinliangis gen. et sp. nov. Despite the immature ontogenetic status of the type materials, D. yingliangis can be diagnosed with autapomorphic traits in the cranial caputegulae (such as double horns on the quadratojugal) and extensive gular osteoderms. Morphologically, it is intermediate between the chronologically older ankylosaurids from Asia (e.g., Crichtonpelta and Jinyunpelta) and derived post-Cenomanian ankylosaurines (e.g., Pinacosaurus). Phylogenetic analyses broadly corroborate this assessment. The new taxon either falls in the grade of Asian ankylosaurines proximal to the lineages of derived forms or forms a sister lineage to Pinacosaurus. Based on these insights, Datai makes a significant addition to the early Late Cretaceous vertebrate fauna from southeastern China and highlights the future potential in this region for improved understanding of the origin and early evolution of ankylosaurines.